Analysing the impact of agricultural landownership on poverty and food security in sri lanka a household level econometric analysis - Deyshappriya, N.P.R.; Abeyweera, G.H.; Ranasinghe, J.P.R.C.; Kulathilake, C.J.P (University of Jaffna, 2019)
This study examines the impact of agricultural landownership on poverty and food security in Sri Lanka. The current study enriches the literature by extending traditional two way poverty classification into four groups: Extremely Poor, Poor, Vulnerable Non-Poor and Non-Poor and quantifies the impact of agricultural landownership on each type of poverty. Similarly, the impact of agricultural landownership on food security is also estimated considering the four types of food security such as, Extremely Food Insecure, Food Insecure, Vulnerable to Food Insecure and Food Secure, based on Minimum Dietary Energy Requirements. The analysis is based on the secondary data from the Household Income and Expenditure Survey (HIES) and two Ordered Probit Models were estimated for poverty and food security to accomplish the objectives of the given study. The results highlight that the probability of being non-poor of the households with agriculture land is higher by 6.42% compared to the households without agricultural lands. Similarly, having agriculture land also reduces the probability of being extremely poor, poor and vulnerable to poverty by 0.1%, 2.2% and 4.1% respectively.In addition, the empirical findings indicate that ownership of agricultural land lessens the probability of being extremely food insecure (0.8%), food insecure (1.4%) and vulnerable to food insecure (0.7%). Moreover, the probability of being food secure of the households with agricultural lands is higher by 0.9% compared to the households without agricultural lands. Therefore, the study emphasizes the significance of agricultural landownership to mitigate the poverty and food insecurity which ultimately enhancesthe household wellbeing. Hence, the current study strongly recommends implementing appropriate policies to address land-right related issues faced by developing countries ensuring long term wellbeing of the households.
Keywords: Landownership; Poverty; Food security; Minimum dietary energy requirement; Ordered probit model